3q26/EVI1 rearrangements in myeloid hemopathies: a cytogenetic review. (June 2015) - De Braekeleer, Marc; Le Bris, Marie-Josée; De Braekeleer, Etienne; Basinko, Audrey; Morel, Frédéric; Douet-Guilbert, Nathalie
ABSTRACT : The EVI1 gene, located in chromosomal band 3q26, is a transcription factor that has stem cell-specific expression pattern and is essential for the regulation of self-renewal of hematopoietic stem cells. It is now recognized as one of the dominant oncogenes associated with myeloid leukemia. EVI1 overexpression is associated with minimal to no response to chemotherapy and poor clinical outcome. Several chromosomal rearrangements involving band 3q26 are known to induce EVI1 overexpression. They are mainly found in acute myeloid leukemia and blastic phase of Philadelphia chromosome-positive chronic myeloid leukemia, more rarely in myelodysplastic syndromes. They include inv(3)(q21q26), t(3;3)(q21;q26), t(3;21)(q26;q22), t(3;12)(q26;p13) and t(2;3)(p15–23;q26). However, many other chromosomal rearrangements involving 3q26/ EVI1 have been identified. The precise molecular event has not been elucidated in the majority of these chromosomal abnormalities and most gene partners remain unknown.